BET404 – Parasite of Aquatic Animals (Parasit Haiwan Akuatik) - February - March 2022 - PPSKJ, Pusat Pengajian Sains Kajihayat (2022)
First Semester Examination 2021/2022 Academic Session February/March 2022 BET404 – Parasite of Aquatic Animals (Parasit Haiwan Akuatik) Duration: 2 hours (Masa: 2 jam)